Media Online Terhadap Elektabilitas Ganjar - Kusuma, Adhi; Rosadi, Riki; Mahreza, Galang Muhammad; Sakiki, Sakiki; Aliansyah, Dhean (Professional: Jurnal Komunikasi dan Administrasi Publik, 2024)
This research aims to find, analyze online media towards Ganjar's electability. The focus of discussion in this research is on defining the nature of language, Ganjar's electability, Ganjar's social media management, Ganjar's political public relations through social media. The writing method used in this research is descriptive analytic, which is a method that describes or provides an overview of the subject under study using data or samples collected in such a way, without analysis to draw conclusions about the public. Ganjar Pranowo's popularity and electability were at their lowest point when he was first announced as a candidate for Central Java governor. Dian said the popularity problem caused by the pairing of Ganjar and Heru in Central Java in early 2013 was considered insufficient, but raised the possibility that PDIP votes would be split with a parliamentary victory.